Modeling Terrorism Risk to the Air Transportation System - Morral, Andrew R.; Price, Carter C.; Ortiz, David S.; Wilson, Bradley; LaTourrette, Tom (RAND Corporation, 2023)
RAND evaluated a terrorism risk modeling tool developed by the Transportation Security Administration and Boeing to help guide program planning for aviation security. This tool—the Risk Management Analysis Tool, or RMAT—is used by TSA to estimate the terrorism risk-reduction benefits attributable to new and existing security programs, technologies, and procedures.